2019
DOI: 10.1101/572198
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The evolution and phylodynamics of serotype A and SAT2 foot-and-mouth disease viruses in endemic regions of Africa

Abstract: Foot-and-mouth disease (FMD) is a major livestock disease with direct clinical impacts as well as indirect trade implications. Control through vaccination and stamping-out has successfully reduced or eradicated the disease from Europe and large parts of South America. However, sub-Saharan Africa remains endemically affected with 5/7 serotypes currently known to be circulating across the continent. This has significant implications both locally for livestock production and poverty reduction but also globally as… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…absence of coinfections) and factors related with on‐farm biosecurity (i.e. presence of a line of separation, cleaning and disinfection station) (Altizer, Bartel, & Han, 2011; Lycett et al., 2019; Rappole et al., 2006). Thus, further studies are needed to evaluate how biosecurity practices and overall pig health may contribute in slowing or accelerating PRRSV spread, results of these assessments can be used to predict the most effective biosecurity measures and optimize control strategies that go beyond PRRSV (Silva et al., 2019), not to mention current diseases that pose large‐scale biosecurity threats to the U.S swine health such as African Swine Fever.…”
Section: Discussionmentioning
confidence: 99%
“…absence of coinfections) and factors related with on‐farm biosecurity (i.e. presence of a line of separation, cleaning and disinfection station) (Altizer, Bartel, & Han, 2011; Lycett et al., 2019; Rappole et al., 2006). Thus, further studies are needed to evaluate how biosecurity practices and overall pig health may contribute in slowing or accelerating PRRSV spread, results of these assessments can be used to predict the most effective biosecurity measures and optimize control strategies that go beyond PRRSV (Silva et al., 2019), not to mention current diseases that pose large‐scale biosecurity threats to the U.S swine health such as African Swine Fever.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, SAT2 has the highest amino acid substitution per year at this site, serotype A having less, and serotype O the least. Similarly, Lycett et al (21) demonstrated genetic diversity between the topotype clades of SAT2 in sub-Saharan African isolates indicated by a large number of amino acid substitutions and large average pairwise distances between sequences from one topotype to another. Ullah et al (37) suggested that eight amino acid substitutions in the G-H loop of VP1 of the locally circulating FMDV Asia1 serotype may be a cause of vaccination failure.…”
Section: Discussionmentioning
confidence: 88%
“…The study of the evolutionary history and dynamics of FMD viruses along boundaries, in different countries or at continent level is important for better understanding of the basic epidemiological aspects of the virus and the geographical basis of the functional divergence of the virus serotypes (3,14,17,18,21,35,36). However, with recovery of live virus 28 days after acute infection and the persistence of FMDV in cattle in the oropharynx for years (3,26), local strains of the viruses evolve with different immunological identity.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Dellicour et al (2018) demonstrated that major urban areas were crucial in dissemination of the 2014–2015 West Africa Ebola virus outbreak, Lu et al (2017) identified geographic hot spots for diffusion of avian influenza virus in China, and Streicker et al (2016) predicted invasion routes of vampire bat rabies in South America. As sequencing technologies become more accessible, opportunities for constructing a more comprehensive view of the epidemiology of viruses, including FMDV, are becoming more abundant (Knight‐Jones et al, 2016b; Lycett et al, 2019).…”
Section: Introductionmentioning
confidence: 99%